Targeting the RAS axis alleviates silicotic fibrosis and Ang II-induced myofibroblast differentiation via inhibition of the hedgehog signaling pathway. (1st October 2019) - Zhang, Bonan; Xu, Hong; Zhang, Yi; Yi, Xue; Zhang, Guizhen; Zhang, Xin; Xu, Dingjie; Gao, Xuemin; Li, Shifeng; Zhu, Ying; Zhang, Hui; Wei, Zhongqiu; et al.
Graphical abstract: Highlights: Hedgehog was reemerged in pneumoconiosis autopsy specimen and BALF. Activation of Hedgehog promoted silicosis in rat. Activation of Hedgehog promoted Ang II-induced myofibroblasts differentiation. GANT61 inhibited Ang II-induced myofibroblasts differentiation. Targeting RAS alleviated silicosis by inhibiting Hedgehog in vivo and in vitro . Abstract: The hedgehog (HH) signaling pathway plays an important role in lung development, but its significance in silicosis is unclear. We showed that in human coal pneumoconiosis autopsy specimens, Sonic Hedgehog (SHH) and the Glioma-associated oncogene homolog transcription factors family (GLI) 1 proteins were up-regulated, whereas Patch-1 (PTC) was down-regulated. The protein levels of SHH, smoothened (SMO), GLI1, GLI2, α-smooth muscle actin (α-SMA) and collagen type Ⅰ (Col Ⅰ) were also elevated gradually in the bronchoalveolar lavage fluid (BALF) of different stages of coal pneumoconiosis patients, dynamic silica-inhalation rat lung tissue and MRC-5 cells induced by Ang II at different time points, whereas the PTC and GLI3 levels were diminished gradually. Ac-SDKP, an active peptide of renin-angiotensin system (RAS), is an anti-fibrotic tetrapeptide. Targeting RAS axis also has anti-silicotic fibrosis effects. However, their roles on the HH pathway are still unknown. Here, we reported that Ac-SDKP + Captopril, Ac-SDKP, Captopril, or Ang (1–7) could alleviate silicotic fibrosis and collagen deposition, as well as improve the lung functions of silicotic rat. These treatments decreased the expression of SHH, SMO, GLI1, GLI2, α-SMA, and Col Ⅰ and increased the expression of PTC and GLI3 on both the silicotic rat lung tissue and MRC-5 cells induced by Ang II. We also reported that Ang II may promote myofibroblast differentiation via the GLI1 transcription factor and independently of the SMO receptor.